KELOMPOK WANITA TANI DAN UPAYA MEMBANGUN RUANG EKONOMI DI DESA NGANCAR KECAMATAN PLAOSAN KABUPATEN MAGETAN - Heryanto Susilo; Dany Nasrullah; Dina Rahmawati (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2023)
This research aims to determine the implementation of empowerment of the Seruni Women Farmers Group (KWT) in Ngancar Village, Plaosan District, Magetan Regency as an effort to improve the local community's economy. This research uses a descriptive qualitative approach. This research was located in Ngancar Village, RT/RW 13/02, Plaosan District, Magetan Regency. Data collection was carried out using observation techniques, questionnaires to 67 respondents, and documentation. The techniques used in data analysis are data reduction, data display, and drawing conclusions. The results of the research show that the implementation of empowerment for KWT Seruni was carried out through several stages, starting from providing material on how to make noodles from those equipped with facilities in the form of the necessary tools to providing material on packing by conducting a comparative study with MSMEs in Malang. This empowerment program can help Geyong Hamlet female farmers increase their income through the production of vegetable-based food. Keywords: Empowerment, Farmer Women’s Group, Economic Improvement